2012
DOI: 10.1007/s00210-012-0735-1
|View full text |Cite
|
Sign up to set email alerts
|

Protective role of somatostatin receptor 2 against retinal degeneration in response to hypoxia

Abstract: In mouse retinal explants, octreotide, a somatostatin [somatotropin release-inhibiting factor (SRIF)] receptor 2 (sst(2)) agonist, prevents the hypoxia-induced vascular endothelial growth factor upregulation. In mice with oxygen-induced retinopathy (OIR), a model of retinopathy of prematurity, either sst(2) overexpression or octreotide have been found to limit hypoxia-induced angiogenic processes. Here, we investigated whether sst(2) influences retinal degeneration in response to hypoxia in wild-type (WT), sst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 86 publications
(150 reference statements)
4
14
1
Order By: Relevance
“…However, the inhibitory effect of AKBA on the neovascular response does not seem to result in improved visual function, as indicated by the ERG data which are similar in vehicle-and in AKBA-treated OIR retinas. This is different from the results obtained in previous studies, where other substances with documented anti-angiogenic effects in OIR retinas were also observed to rescue, at least in part, the electroretinographic responses (Dal Monte et al, 2012a;Martini et al, 2011). However, there is also evidence indicating that treatments preventing pathological angiogenesis may not necessarily prevent retinal dysfunction (Hatzopoulos et al, 2014).…”
Section: Akba Is Well Tolerated By the Retina And Reduces Retinal Neocontrasting
confidence: 98%
See 2 more Smart Citations
“…However, the inhibitory effect of AKBA on the neovascular response does not seem to result in improved visual function, as indicated by the ERG data which are similar in vehicle-and in AKBA-treated OIR retinas. This is different from the results obtained in previous studies, where other substances with documented anti-angiogenic effects in OIR retinas were also observed to rescue, at least in part, the electroretinographic responses (Dal Monte et al, 2012a;Martini et al, 2011). However, there is also evidence indicating that treatments preventing pathological angiogenesis may not necessarily prevent retinal dysfunction (Hatzopoulos et al, 2014).…”
Section: Akba Is Well Tolerated By the Retina And Reduces Retinal Neocontrasting
confidence: 98%
“…6CeE, the amplitude of a-and b-waves, as well as SOPs, at light intensity of 1 log cd-s m À2 are reported. As previously described Vessey et al, 2011;Dal Monte et al, 2012a), OIR mice displayed significantly reduced a-and b-wave amplitudes, as well as SOPs, compared with control mice (Fig. 5CeE).…”
Section: Akba Does Not Affect Retinal Cell Survival or Retinal Functionsupporting
confidence: 84%
See 1 more Smart Citation
“…The present study by Dal Monte et al provides possible pathways by which β 3 -adrenoceptor agonists/antagonists may modulate VEGF release through NO in vascular endothelial cells and surrounding cells, including neuroglial cells (Dal Monte et al 2013). This work expands on previous work of the same group on hypoxia in the retina (Dal Monte et al 2012a) and other tissues .…”
supporting
confidence: 80%
“…Our results indicated that pretreatment with the selective SST‐depleting agent cysteamine or using an SST receptor antagonist, such as c‐SOM, to some extent, reversed the effects of CAP, illustrating that the endogenous SST released into circulation played effective roles in anti‐inflammation and neuroprotection. Many studies have established that exogenous SST or synthetic analogues exert anti‐inflammatory and/or neuroprotective effects . Szolcsanyi et al.…”
Section: Discussionmentioning
confidence: 99%